Late Development of a Lamellar Macular hole after the Spontaneous Separation of Vitreoretinal Traction: Case Report. Issue 6 (November 2016) - Rodríguez, Alvaro; Rodríguez, Francisco J.; Valencia, Marcela; Castaño, Claudia
Purpose: To report a case of epiretinal macular membrane and a lamellar macular hole developing after the spontaneous separation of an idiopathic vitreoretinal traction. Methods: Retrospective, observational, long follow-up of a case evaluated and documented with optical coherence tomography and managed with current therapies including pars plana vitrectomy. Results: Good anatomic and functional results with stable 20/30 best-corrected visual acuity. Conclusions: The natural course of idiopathic vitreomacular traction has been documented during prolonged observation after its spontaneous separation from the fovea leading to the development of an epiretinal membrane and a lamellar macular hole.